Development of SMART-P to improve parental locus of control and children’s social-emotional development - Evania Yafie; Zakiah Mohamad Ashari; Norazrena Abu Samah; Diana Setyaningsih; Dessy Putri Wahyuningtyas; I Gusti Lanang Agung Wiranata (International Journal of Evaluation and Research in Education (IJERE), 2024)
Child social-emotional development is improved by parental locus of control. Parents with a healthy locus of control can teach children about social-emotional development. Parents require training to improve their parenting skills. This study will create, administer, and evaluate the seamless mobile-assisted real training for parent (SMART-P) application on parental locus of control and children’s social and emotional development. The mixmethod study used an analysis, design, development, implementation, and evaluation (ADDIE) model and experimental quantification research strategy. An explanatory study with a non-equivalent control group design and control-experiment classes is used. This study includes analysis, design, development, research instrument development, implementation, and assessment. This study sampled 150 parents of 4-year-olds and 6 experts, including 714 from Posyandu (Integrated Service Post) in five Malang City areas. The data was collected via questionnaires and observation checklists. This study analyzes data using descriptive percentages and SPSS. The findings showed that i) SMART-P is valid and acceptable as a training medium; ii) parental locus of parental control is significantly influenced before and after receiving SMART-P parenting training; iii) children’s social and emotional development is significantly impacted before and after parents receive care using the program; and iv) there is a significant difference between the experimental and control groups in the influence on parental continuous. SMART-P parenting research is needed to enhance parental locus of control and children’s social-emotional development